c-Abl regulates a synaptic plasticity-related transcriptional program involved in memory and learning - Gonzalez-Martin, Adrian; Moyano, Tomas; Gutierrez, Daniela A.; Carvajal, Franciso J.; Cerpa, Waldo; Hanley, Jonathan G.; Gutierrez, Rodrigo A.; Alvarez, Alejandra R. (My University, 2021)
Memory consolidation requires activation of a gene expression program that allows de novo protein synthesis. But the molecular mechanisms that favour or restrict that program are poorly understood. The kinase c-Abl can modulate gene expression through transcription factors and chromatin modifiers. Here, we show that c-Abl ablation in the brain improves learning acquisition and memory consolidation in mice. Its absence also affects gene expression profiles in the mouse hippocampus. We found that genes involved in synaptic plasticity and actin cytoskeleton dynamics, such as Arp2 and Thorase, are up-regulated at the mRNA and protein levels in trained cAbl KO mice and by a chemical-LTP stimulus. Trained c-Abl KO mice also show that dendritic spines are larger than in wild-type mice and present at a higher density. These results indicate that c-Abl kinase is an important part of the mechanism that limits or restricts signalling of relevant gene programs involved in morphological and functional spine changes upon neuronal stimulation.
Keywords: c-abl; memory and learning; transcriptional regulation; synaptic plasticity; spine morphology; hippocampal rnaseq